Evaluating the bushfire resistance of a safe room using full-scale experiments. (March 2023) - Hendawitharana, Sahani; Ariyanayagam, Anthony; Mahendran, Mahen; Steau, Edward
Abstract: To minimise the psychological and physiological impairment due to bushfire losses, safe rooms are identified as one of the last resort solutions. This paper proposes a safe room built with cavity insulated light gauge steel framed walls and roof lined externally with Autoclaved Aerated Concrete panels and internally with fire-rated gypsum plasterboards. Full-scale experiments of the proposed safe room were conducted at an outdoor fire testing facility to investigate its bushfire resistance under flame zone conditions. A two-source bushfire exposure was simulated to replicate an approaching bushfire and a nearby building fire. Internal and external air temperatures, surface temperatures along and across the wall and roof surfaces, heat flux, wind speed and direction were recorded to evaluate the performance of the safe room. The safe room performed well with respect to heat transfer, exhibiting a significant safety margin for 67 min duration. The external building envelope exhibited good thermal shock resistance despite the high heating rate in bushfires compared to building fires. The study was further extended to investigate the performance of the safe room under repeated bushfire exposures where the safe room exhibited similar fire resistance. The results of this study reveal that a safe room solution is feasible and will survive extreme bushfire conditions.